Strategic security : forward thinking for successful executives. - Perois, Jean. ([Place of publication not identified], CRC Press, 2019)
Strategic Security will help security managers, and those aspiring to the position, to think strategically about their job, the culture of their workplace, and the nature of security planning and implementation. Security professionals tend to focus on the immediate (the urgent) rather than the important and essential--too often serving as'firefighters' rather than strategists. This book will help professionals consider their roles, and structure their tasks through a strategic approach without neglecting their career objectives. Few security management books for professionals in the field focus on corporate or industrial security from a strategic perspective. Books on the market normally provide'recipes,' methods or guidelines to develop, plans, policies or procedures. However, many do so without taking into account the personal element that is supposed to apply these methods. In this book, the authors helps readers to consider their own career development in parallel with establishing their organisation security programme. This is fundamental to becoming, and serving as, a quality, effective manager. The element of considering career objectives as part-and-parcel to this is both unique to only this book and vital for long-term career success. The author delineates what makes strategic thinking different in a corporate and security environment. While strategy is crucial in the running of a company, the traditional attitude towards security is that it has to fix issues quickly and at low cost. This is an attitude that no other department would tolerate, but because of its image, security departments sometimes have major issues with buy-in and from top-management. The book covers the necessary level of strategic thinking to put their ideas into practice. Once this is achieved, the strategic process is explained, including the need to build the different steps into this process--and into the overarching business goals of the organisation--will be demonstrated. The book provides numerous hand-on examples of how to formulate and execute the strategic master plan for the organization. The authors draws on his extensive experience and successes to serve as a valuable resource to all security professionals looking to advance their careers in the field.
SpecificMeasurable (Qualitative); How Can Quality Be Measured?; Security Audit on Quality Performance; The Security Survey and Questionnaire; The Influence Indicators; Measurable (Quantitative); The Risk Inventory; Case Study 1: Recurrent Petty Theft in the Office; Case Study 2: Tailgating and Piggybacking; Measurable (Financial); How Much Will It Cost?; Attainable/Achievable/Agreed; Relevant/Realistic/Results Orientated; Time Bound/Time Framed; Principle for Keeping Security Statistics and KPIs; The Collection and Management of Data; Feeding the KPIs: The Need for Relevant Metrics
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; Executives; Strategic planning; Security systems